Fair Value Non-Current Asset, Koneksi Politik, dan Audit Fee - Yeni Anggriani; Helmi Yazid; Muhamad Taqi (AFRE (Accounting and Financial Review), 2020)
This study aims to determine the effect of fair value non-current asset on the determination of audit fee and to know moderating effect of political connection between fair value non -current asset and audit fee in financial companies listed in Indonesia Stock Exchange. The method of research analysis used in this research is descriptive method. Population in this research is financial companies listed in Indonesia Stock Exchange with sample of 25 companies by using purposive sampling method in period 2016-2018. The data used is secondary data collected by documentation technique. In analyzing the data, this study used a test tool of ordinary least square (OLS) analysis and moderation regression analysis (MRA). The result of this research indicates that fair value non-current asset influence audit fee and this research show that the political connection can’t moderate of fair value non-current asset toward audit fee. DOI: https://doi.org/10.26905/afr.v3i2.4708